Oxidative degradation of dyes in water using Co2+/H2O2 and Co2+/peroxymonosulfate - Ling, Sie king; Wang, Shaobin; Peng, Y. (Elsevier, 2010)
Dye degradation using advanced oxidation processes with Co2+/H2O2 and Co2+/peroxymonosulfate (PMS) systems has been investigated. Two types of dyes, basic blue 9 and acid red 183, were employed. Several parameters affecting dye degradation such as Co2+, PMS, H2O2, and dye concentrations were investigated. The optimal ratio of oxidant (PMS, H2O2)/Co2+ for the degradation of two dyes was determined. It is found that dye decomposition is much faster in Co2+/PMS system than in Co2+/H2O2. For Co2+/H2O2, an optimal ratio of H2O2 to Co2+ at 6 is required for the maximum decomposition of the dyes. For Co2+/PMS, higher concentrations of Co2+ and PMS will increase dye degradation rate with an optimal ratio of 3, achieving 95% decolourisation. For basic blue 9, a complete decolourisation can be achieved in 5 min at 0.13 mM Co2+, 0.40 mM PMS and 7 mg/l basic blue 9 while the complete degradation of acid red 183 will be achieved at 30 min at 0.13 mM Co2+, 0.40 mM PMS and 160 mg/l of acid red 183. The degradation of acid red 183 follows the second-order kinetics.